2009
DOI: 10.1111/j.1468-5957.2008.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Investment Banks Value Initial Public Offerings (IPOs)?

Abstract: Abstract:We investigate the valuation and the pricing of initial public offerings (IPOs) by investment banks for a unique dataset of 49 IPOs on Euronext Brussels in the 1993-2001 period. We find that for each IPO several valuation methods are used, of which Discounted Free Cash Flow (DFCF) is the most popular. The offer price is mainly based on DFCF valuation, to which a discount is applied. Our results suggest that DDM tends to underestimate value, while DFCF produces unbiased value estimates. When using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 70 publications
9
62
7
Order By: Relevance
“…However, all these studies use ex-post value estimates produced by researchers to test the accuracy of valuations, and they typically find that IPO firms are overvalued at offer prices relative to their comparables. We are aware of only three other papers investigating the accuracy of the valuation models actually used by investment banks: Cassia et al (2004) in Italy, Roosenboom (2007) in France, and Deloof et al (2009) in Belgium. 1 All three studies take advantage of the extensive disclosure required of companies going public in Continental Europe and confirm that 1 Cassia et al (2004) examined the methods used by underwriters to value 83 IPOs in Italy during the period 1999-2002 and find that relative valuation is the approach more frequently adopted by underwriters (87% of the IPOs), closely followed by DCF (80%).…”
Section: The Valuation Of Iposmentioning
confidence: 98%
See 1 more Smart Citation
“…However, all these studies use ex-post value estimates produced by researchers to test the accuracy of valuations, and they typically find that IPO firms are overvalued at offer prices relative to their comparables. We are aware of only three other papers investigating the accuracy of the valuation models actually used by investment banks: Cassia et al (2004) in Italy, Roosenboom (2007) in France, and Deloof et al (2009) in Belgium. 1 All three studies take advantage of the extensive disclosure required of companies going public in Continental Europe and confirm that 1 Cassia et al (2004) examined the methods used by underwriters to value 83 IPOs in Italy during the period 1999-2002 and find that relative valuation is the approach more frequently adopted by underwriters (87% of the IPOs), closely followed by DCF (80%).…”
Section: The Valuation Of Iposmentioning
confidence: 98%
“…In particular, the DCF model is more frequently used when aggregate stock market returns are high or volatile. Finally, Deloof et al (2009) studied 49 IPOs from the 1993-2001 period on the Brussels Stock Exchange and found that DCF is by far the most popular valuation method, being used to price all IPOs in the sample. the DCF model is widely adopted when valuing firms going public.…”
Section: The Valuation Of Iposmentioning
confidence: 99%
“…Although the underpricing of new equity has been widely researched for over two decades, recent studies have revitalised the interest in the underpricing puzzle (see Chen, Fauver & Yang, 2009, Deloof, Maeseneire & Inghelbrecht, 2009and Rocholl, 2009). This paper investigates the forces that shape price clustering in initial public offerings (IPOs).…”
Section: Introductionmentioning
confidence: 99%
“…This can help to further explain the trade-off between higher (lower) wealth loss and higher (lower) insider retained ownership. However, the intrinsic values computed by underwriters and/or insiders are likely to be subjective (Deloof et al, 2009).…”
Section: Resultsmentioning
confidence: 99%